k = 1 ∏ 4 5 sin ( 2 k ∘ ) = 2 n m
In the equation above, m and n are positive integers, where m is odd.
Determine the value of m − n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Clearly we should use root of unity .Let ω = c o s ( 9 0 2 π ) + i s i n ( 9 0 2 π ) . Then ω 2 k = c o s ( 9 0 k π ) + i s i n ( 9 0 k π ) .
k = 1 ∏ 4 5 s i n ( 9 0 k π ) = k = 1 ∏ 4 5 2 i ω 2 k − ω 2 − k = k = 1 ∏ 4 5 2 i ω 2 k ω k − 1 .
Note that s i n ( 9 0 4 5 π ) = 1 and k = 1 ∏ 4 4 s i n ( 9 0 k π ) = k = 4 6 ∏ 8 9 s i n ( 9 0 k π ) > 0 ,
( k = 1 ∏ 4 5 s i n ( 9 0 k π ) ) 2 = k = 1 ∏ 8 9 s i n ( 9 0 k π ) = k = 1 ∏ 8 9 2 i ω 2 k ω k − 1
= 2 − 8 9 ⋅ k = 1 ∏ 8 9 ( 1 − ω k ) = 2 8 8 4 5 .
The last step relies on the equality n = k = 1 ∏ n − 1 ( 1 − ε k ) ,here ε k = e x p ( n 2 k π i ) .
Thus m = 4 5 , n = 4 4 , m − n = 1 .
Can you explore why n = k = 1 ∏ n − 1 ( 1 − ε k ) ? Or just give me a link, I want to read it! I have seen many of solution like this but the writer just doesn't give the proof.
Log in to reply
It's clear that forall real x≠1: k = 0 ∑ n − 1 x k = x − 1 x n − 1 = x − 1 ∏ k = 0 n − 1 ( x − ε k ) = k = 1 ∏ n − 1 ( x − ε k ) .Then let x → 1 we get n = k = 1 ∏ n − 1 ( 1 − ε k ) (this step may be not rigorous,but I think it's still acceptable).
Problem Loading...
Note Loading...
Set Loading...
From the reference (equation (24)) , we have k = 1 ∏ n − 1 sin ( n k π ) = 2 1 − n n . Then
k = 1 ∏ 8 9 sin ( 9 0 k π ) ⟹ k = 1 ∏ 8 9 sin ( 2 k ∘ ) k = 1 ∏ 4 5 sin ( 2 k ∘ ) k = 4 6 ∏ 8 9 sin ( 2 k ∘ ) k = 1 ∏ 4 5 sin ( 2 k ∘ ) k = 1 ∏ 4 4 sin ( 2 k ∘ ) k = 1 ∏ 4 5 sin ( 2 k ∘ ) k = 1 ∏ 4 5 sin ( 2 k ∘ ) = 2 8 9 9 0 = 2 8 8 4 5 = 2 8 8 4 5 = 2 8 8 4 5 = 2 8 8 4 5 Since sin ( 1 8 0 − x ) ∘ = sin x ∘ Since sin 9 0 ∘ = 1
⟹ k = 1 ∏ 4 5 sin ( 2 k ∘ ) = 2 8 8 4 5 = 2 4 4 4 5
Therefore, m − n = 4 5 − 4 4 = 1 .